The Application of technical aspects of raising swamp buffalo in Pangean sub-district, Kuantan Singingi Regency - Yendraliza Yendraliza; Evi Irawati (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2023)
Buffalo (Baballus buballis) is a large ruminant livestock that has long been known by the people of Indonesia. Pangean sub-district is a sub-district that has a fairly large population of buffalo, namely 876 heads. In general, farms in Pangean District have not implemented the technical aspects of maintenance and there are still many deficiencies that need to be addressed and repaired by breeders. This study aimed to determine the application of technical aspects of maintenance including parts of breeding, housing, feed, health and maintenance management in Pangean District, Kuantan Singingi Regency and the structure of the buffalo population. The method used in this study was a survey method with 151 farmers as respondents. The variables in the study were the profile of respondents, aspects of breeding, housing, feed, health, maintenance management, and population structure of buffaloes. The results of this study indicate that the characteristics of the respondents consisted of 79.47% male and 20.53% female, the age of the breeders ranged from 32-68 years, 35.76% graduated from high school, had livestock farming experience of 1-13 years, and the main occupation was as farmers 49.01%. Implementation of technical aspects of maintenance with the following percentages: nursery aspect 42.05%, housing aspect 58.68%, feed aspect 33.33%, health aspect 73.51%, and maintenance management aspect 62.03%. It can be concluded that overall the technical aspects of raising buffalo livestock in Pangean District, Kuantan Singingi Regency, with an unfavorable percentage of 53.92%. The population structure of buffalo in the Pangean District is dominated by female livestock.